(untitled) (Iraqi Journal of Medical Sciences, 2009)
Background: Pregnancy induced hypertensive disorders are common complications responsible for fetal, neonatal and maternal morbidity. Current hypothesis regarding the pathophysiologic mechanisms of pregnancy induced hypertension point to early placental abnormalities. Objective: To determine whether measurement of serum human chorionic gonadotropin might reflect a different secretory trophoblastic response of preeclampsia. Study design: A prospective study. Setting: Department of Obstetrics & Gynecology in Al-Kadimyia Teaching Hospital. Patients and methods: A total of 80 pregnant women were studied during the period from October through July 2005. They included 40 patients with severe peeclampsia were matched with 40 healthy normotensive women in the third trimester with singleton pregnancies and without congenital malformations. Serum levels of β-hCG were measured by immunoenzymometric assay before delivery and neonatal outcome was recorded. Results: Serum β-hCG levels were found to be significantly higher in severe preeclamptic women compared with controls (P<0.05). Elevated β-hCG levels in severe preeclampsia was associated with higher rate of preterm delivery (50% vs. 7.5%), higher rate of intrauterine growth restriction of birth weight <10th centile (47.5% vs. 5%), higher rate of low birth weight of < 2500 gm (70.25% vs. 12.5%) and higher rate of fetal death (7.5% vs. 0). Conclusion: Elevated serum β-hCG levels in severely preeclamptic women reflect a significantly pathologic change and abnormal secretory function of the placenta with subsequent pregnancy outcome. Keywords: preeclampsia, Human chorionic gonadotrophin, pregnancy